2013
DOI: 10.1093/hmg/ddt402
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of the KXGS motifs in tau is a critical determinant in modulation of tau aggregation and clearance

Abstract: The accumulation of hyperphosphorylated tau in neurofibrillary tangles (NFTs) is a neuropathological hallmark of tauopathies, including Alzheimer's disease (AD) and chronic traumatic encephalopathy, but effective therapies directly targeting the tau protein are currently lacking. Herein, we describe a novel mechanism in which the acetylation of tau on KXGS motifs inhibits phosphorylation on this same motif, and also prevents tau aggregation. Using a site-specific antibody to detect acetylation of KXGS motifs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
288
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(302 citation statements)
references
References 45 publications
13
288
1
Order By: Relevance
“…However, another study showed that the expression of histone deacetylase 6 (HDAC6) positively correlates with tau burden, while a decrease in HDAC6 activity or expression promotes tau clearance [67] , and its levels have also been shown to be elevated in the brains of patients with AD and transgenic mice [68,69] . Thus, a better understanding of the relationship of these acetylation residues with phosphorylation could be crucial to identify potential targets for therapy in AD and other tauopathies.…”
Section: Other Post-translational Modifi Cationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another study showed that the expression of histone deacetylase 6 (HDAC6) positively correlates with tau burden, while a decrease in HDAC6 activity or expression promotes tau clearance [67] , and its levels have also been shown to be elevated in the brains of patients with AD and transgenic mice [68,69] . Thus, a better understanding of the relationship of these acetylation residues with phosphorylation could be crucial to identify potential targets for therapy in AD and other tauopathies.…”
Section: Other Post-translational Modifi Cationsmentioning
confidence: 99%
“…Using antibodies specific for acetylated tau, it has been shown that tau acetylation is elevated in patients at early and moderate Braak stages of tauopathy [66] . Meanwhile, they demonstrated that deacetylase SIRT1 deficiency leads to hyperacetylation of tau and accumulation of p-tau, while in contrast, promoting tau deacetylation eliminates p-tau.However, another study showed that the expression of histone deacetylase 6 (HDAC6) positively correlates Cindy Beharry, et al Tau-induced neurodegeneration: mechanisms and targets 349 with tau burden, while a decrease in HDAC6 activity or expression promotes tau clearance [67] , and its levels have also been shown to be elevated in the brains of patients with AD and transgenic mice [68,69] . Thus, a better understanding of the relationship of these acetylation residues with phosphorylation could be crucial to identify potential targets for therapy in AD and other tauopathies.…”
mentioning
confidence: 99%
“…Acetylation of tau in neurons is mediated by p300 acetyltransferase and CREB-binding protein (CBP) possibly at different sites Brought to you by | MIT Libraries Authenticated Download Date | 5/12/18 1:47 PM (Cohen et al, 2011;Cook et al, 2014). Experiments carried out by Min et al (2010) suggested that the deacetylase sirtuin 1 (SIRT1), which is localized exclusively in neurons, may be involved in tau deacetylation.…”
Section: Tau Acetylation and The Role Of Hdac6mentioning
confidence: 99%
“…As HDAC inhibitors, these curcuminoids may alter phosphorylation 30 and/ or reduce the stability of tau protein 31,32 , resulting in decreased clinical features of tauopathies, a class of neurodegenerative diseases associated with the pathological aggregation of tau protein in the human brain. The best known of these illnesses is Alzheimer's disease, wherein tau protein is deposited within neurons in the form of neurofibrillary tangles.These curcuminoids as HDAC inhibitors couldal so suppress cancer by inducing the G1/S phase arrest primarily through transcriptional changes in cell cycle regulatory genes 33 .…”
Section: Curcumin Demethoxy Curcumin and Bisdemethoxy Curcumin As Pomentioning
confidence: 99%